Step-by-step explanation
From the statement, we know that:
• ∠ABC ≅ ∠EFG,
• ∠ABC = (4x + 3)°,
• ∠EFG = (2x + 11)°.
(1) Using the data from above, we have:
![\begin{gathered} ∠ABC\cong∠EFG, \\ (4x+3)\degree=(2x+11)\degree, \\ 4x+3=2x+11. \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/gojx1izyp0m641owuupbux3rmd2rj730xl.png)
(2) Solving for x the last equation:
![\begin{gathered} 4x+3-2x=11, \\ 2x+3=11, \\ 2x=11-3, \\ 2x=8, \\ x=(8)/(2)=4. \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1anbn4u59jm7zhjbe97cy5gro53ik7dvtz.png)
(3) Replacing the value x = 4 in the equations of the first angle, we get:
![∠ABC=(4\cdot4+3)°=(16+3)\degree=19\degree.](https://img.qammunity.org/2023/formulas/mathematics/college/mhd2n1d1o66tfo9k18fq5bt7on8ei1nuh9.png)
Answer
m∠ABC = m∠EFG = 19°